2008
DOI: 10.1007/s00277-008-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

Citrate artificially masks the haemostatic effect of recombinant factor VIIa in dilutional coagulopathy

Abstract: International audienceMost often, thrombelastographic analyses are carried out using citrated blood and re-calcification. However, calcium chelation may affect dynamics of tissue-factor-initiated thrombin generation. The present study investigates the effect of sample anticoagulant on the response of a colloid induced dilutional coagulopathy model to recombinant activated factor VII (rFVIIa) as measured by thrombelastography. Thrombelastographic evaluation of whole blood coagulation activated with minute amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The present findings concur with other investigations demonstrating that contact‐pathway activation interferes with coagulation measurements initiated by low concentrations of TF (Luddington & Baglin, 2004; Mann et al , 2007). We found an increase in the effect of rFVIIa and NN1731 in the presence of CTI, supporting previous observations in haemodiluted blood (Fenger‐Eriksen et al , 2009). The exact mechanisms of the observed influence of CTI on the response pattern of rFVIIa and NN1731 were beyond the scope of this investigation.…”
Section: Thromboelastometric Coagulation Data Obtained From Corn Trysupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings concur with other investigations demonstrating that contact‐pathway activation interferes with coagulation measurements initiated by low concentrations of TF (Luddington & Baglin, 2004; Mann et al , 2007). We found an increase in the effect of rFVIIa and NN1731 in the presence of CTI, supporting previous observations in haemodiluted blood (Fenger‐Eriksen et al , 2009). The exact mechanisms of the observed influence of CTI on the response pattern of rFVIIa and NN1731 were beyond the scope of this investigation.…”
Section: Thromboelastometric Coagulation Data Obtained From Corn Trysupporting
confidence: 92%
“…We recently reported on the effect of in vitro addition of rFVIIa and NN1731 to blood from children with thrombocytopenia due to chemotherapy and in a laboratory model of thrombocytopenia in citrated WB (Larsen et al , 2009). Our group has also studied rFVIIa in a thromboelastometric model of haemodilution, where an effect only was demonstrable in the presence of CTI whereas there was apparently no effect when using citrated WB (Fenger‐Eriksen et al , 2009). The recent study in thrombocytopenia (Larsen et al , 2009) was performed without the use of CTI, hence, it may be speculated that the effect of rFVIIa and NN1731 has been underestimated.…”
Section: Thromboelastometric Coagulation Data Obtained From Corn Trymentioning
confidence: 99%
“…1A). While a number of recent studies have addressed the effects of dilution on these parameters, 17‐20 it is still unknown which of the five parameters displays the highest sensitivity to blood plasma dilution. Furthermore, some of the studies of dilution‐induced effects on thrombin generation parameters have reported disparate results (e.g., see De Smedt et al, 17 Schols et al, 19,20 Dunbar and Chandler 21 ).…”
mentioning
confidence: 99%
“…Slightly impractical as this may be, citrated blood has been implied to interfere with thrombin generation and thus produce errors in coagulation assessment, making native blood a more attractive choice in this regard [26,27].…”
Section: Coagulation Monitoringmentioning
confidence: 99%